Analysis of Social Performance in the Spanish Financial Industry Through Public Data. A Proposal - de la Cuesta-González, Marta (Journal of business ethics, 2006)
Banking firms are becoming increasingly aware that their clients’ management of environmental and social risks may in term threaten their own business as lenders and investors. In addition, stakeholders are requiring banks to improve their social performance. As a result, some banks are developing corporate social responsibility (CSR) policies and management systems to reduce potential risks and improve their performance. In the Spanish financial system, half of the banking firms are savings banks, most of which have always used some Corporate Social Responsibility (CSR) criteria in their management. Private Banks have only recently started to integrate social aspects in their performance. However, no formal analysis has been carried out on the impact of CSR strategies. Various initiatives have been launched nationally and internationally to include the social dimension in management systems. The purpose of this research is to analyse the social performance of the main Spanish financial companies through public data such as social or sustainability reports and media sources. In order to do this, we need to determine which CSR criteria most greatly affect banking firms and to choose the most accurate quantitative and qualitative indicators to measure social performance.